3 - The National Project as a Public Administration Concept: The Problematic of State Building in the Search for New Development Paradigms in Africa - Lumumba-Kasongo, Tukumbi (Africa Development, 2021)
In the centre of the debate regarding the values and importance of decolonisation, development thought, and the post-colonial state- building in Africa, the question of the national project is central. In theory, a national project, as either an imaginary concept of the political elite, a tool of political domination, or a real complex embodiment of the mobilisation of ideas and thoughts; it is about governance. It implies the existence of some dimensions of political, economic and cultural nationalism both in its policy framework and political basis. At the time of political independence, most of the African political regimes, regardless of the nature of their ideologies, history of their state formations, and how they gained political independence, adopted and/ or created some forms of national projects as the foundation of their social and economic platforms. However, it is generally known that African states have produced a relatively weak, fragmented, individualised and personalised public administration based on ambiguous and confused national projects. In Africa, even the reactionary regimes have claimed to be nationalistic. Why has this consistently been the case? There are various interpretations of African national projects, which became the policy blueprints, through which the African political elites and the people were, in principle, supposed to be connected with one another in exploring new developmental models. Although many studies have been conducted on some aspects of the role of national projects and public administrations in projecting social progress in Africa, so far there have not been enough studies that historically examine the notion of national projects and their relationship with public administration. I intend to critically examine the historicity of the concept of national project as defined and projected through various selected types of African political regimes and social movements, identify their common similarities, if any, and compare their ultimate political ends. Secondly, using historical structural and comparative perspectives, I analyse how the notion of public administration was built in, and developed within, the national project. It is argued that no contemporary state is able to effectively render services that, in the long run, can be translated into solid infrastructures without building a public administration that is relevant and appropriate as part of the state’s national project. Public administration should be an apparatus of the public space in which integrative ideas, public management, societal values, and collective citizenry are articulated. I am also interested in understanding the nature of the relationship between the national project as an ideology of the state and the public administration as the functional foundation of the state in Africa and see how this relationship can foster the thoughts about the notion of public agenda or the public space. Behind this analytical reflection, the broader issue is the idea that the concept of the ‘political public’ defined through the relationship between national projects, public administrations, and the civil societies should be viewed as the cement for the collective political culture.